Conservative treatment of acquired oesophageal strictures by endoscopic‐guided balloon dilation in two horses. (25th September 2015) - Stucchi, L.; Zucca, E.; Stancari, G.; Conturba, B.; Roncon, S.; Ferro, E.; Gualtieri, M.; Ferrucci, F.
Summary: Oesophageal stricture is an uncommon condition in horses that results in an obstructive syndrome with regurgitation of food and possible aspiration pneumonia. Currently, in both human and small animal practice, one of the preferred treatment options for oesophageal strictures consists of pneumatic or hydrostatic balloon dilation. The aim of this article is to report 2 cases of severe oesophageal stricture in the horse, successfully treated with endoscopic‐guided hydrostatic balloon dilation.